2000
DOI: 10.1002/hep.510310109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propranolol on the factors promoting bacterial translocation in cirrhotic rats with ascites

Abstract: Bacterial translocation appears to be an important mechanism in the pathogenesis of spontaneous infections in cirrhosis. Cirrhotic patients are commonly treated with ␤-adrenoceptor blockers, but the impact of this treatment in the factors promoting bacterial translocation has not been investigated. This study was aimed at investigating in cirrhotic rats with ascites the effect of propranolol on intestinal bacterial load, transit, and permeability of the bowel and on the rate of bacterial translocation. Bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
168
0
15

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(190 citation statements)
references
References 29 publications
(55 reference statements)
7
168
0
15
Order By: Relevance
“…42,43 Recent studies have shown that bacterial overgrowth and bacterial translocation can also be decreased in experimental cirrhosis by accelerating intestinal transit with cisapride 14 or with propranolol. 44 However, cisapride can produce QT interval prolongation and ventricular arrhythmias. 45 Propranolol cannot be used in all cirrhotic patients and is also known to sometimes have severe adverse effects in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Recent studies have shown that bacterial overgrowth and bacterial translocation can also be decreased in experimental cirrhosis by accelerating intestinal transit with cisapride 14 or with propranolol. 44 However, cisapride can produce QT interval prolongation and ventricular arrhythmias. 45 Propranolol cannot be used in all cirrhotic patients and is also known to sometimes have severe adverse effects in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Increased extraintestinal translocation of Gram-positive bacterial antigens would be expected in such circumstances, given experiences in experimental animals. 43,44 Indeed, lipoteichoic acid, a component of Gram-positive bacteria, has recently been found in liver tissue of cirrhotic patients, presumably as a consequence of extraintestinal translocation from the gut lumen. 27 We found evidence that Gram-positive gut flora may influence systemic TLR expression, serum TNF-␣ levels, and in vitro TNF-␣ production in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] In animal models of LC, portal hypertension and intestinal hypo-mobility lead to bacterial overgrowth in the small bowel and is considered the primum movens of translocation in these models. 30 In a clinical study of 24 patients with liver cirrhosis the bacterial overgrowth was enhanced by portal hypertension, as suggested by animal models. 31 In addition progressive intestinal dysbiosis was identified in patients with LC especially in advanced stages of the disease.…”
Section: Pathophysiology Of Bsis In Patients With Liver Cirrhosis: Inmentioning
confidence: 96%